2018
DOI: 10.33145/2304-8336-2018-23-331-350
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Biological Markers Induced by Ionizing Radiation at the Late Period After Exposure in a Wide Range of Doses

Abstract: Мета. Визначити біологічні маркери радіаційного ураження у віддаленому періоді після опромінення у широ кому інтервалі доз.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…29 On the other hand, in comparison to other Category B groups, Group VIII showed the lowest serum TNF-α level, implicating that HD-IR alone cannot be considered an immunosuppressive tool. Earlier investigations have concluded that high and low IR can activate the transcription and the secretion of IL-2, IFN-γ, and TNF-α; 39 nevertheless, this activation appeared stronger with high IR doses than with low IR doses. 40,41…”
Section: Discussionmentioning
confidence: 82%
“…29 On the other hand, in comparison to other Category B groups, Group VIII showed the lowest serum TNF-α level, implicating that HD-IR alone cannot be considered an immunosuppressive tool. Earlier investigations have concluded that high and low IR can activate the transcription and the secretion of IL-2, IFN-γ, and TNF-α; 39 nevertheless, this activation appeared stronger with high IR doses than with low IR doses. 40,41…”
Section: Discussionmentioning
confidence: 82%
“…Priority data were obtained regarding long-term radiation-induced changes in gene expression and polymorphism, genome instability, and cellular senescence in chronic somatic pathology in persons chronically exposed to a wide range of doses. BCL2, SERPINB9, CDKN2A, STAT3, TP53, MCF2L gene changes have been established [20]. Methods of molecular epidemiology have been introduced in patients with radiation-induced leukemia [21].…”
Section: Resultsmentioning
confidence: 99%
“…They found decreased CD4+/CD8+ ratios and increased Tregs in 56% of the studied clean-up workers, especially in those exposed to low doses. Interestingly, the authors showed that the decrease in the level of B cells and activated T cells correlated with the increase in interleukin (IL)-1β levels in individuals exposed to doses below 100 mSv ( Ilienko et al, 2018 ). Oradovskaia et al studied a cohort of clean-up workers who developed different malignant diseases and identified typical immune parameter changes in these people 1–3 years before the manifestation of cancer.…”
Section: Human Biomonitoring and Epidemiological Data On Low Dose Radiation-induced Immunological Changesmentioning
confidence: 99%